ANALISIS YURIDIS TERHADAP TERBITNYA AKTA JUAL BELI (AJB) PADA TANAH YANG MASIH BERSERTIFIKAT ATAS NAMA PIHAK KETIGA DAN DALAM PENGUASAAN PIHAK RENTENIR, STUDI KASUS DARI PERSPEKTIF KORBAN - Muh Saeful Bahri; Ahmad Muhaimin Aziz; Gagah Kencana; Akhmad Fadli (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines the issuance of three Deeds of Sale and Purchase (Akta Jual Beli/AJB) for subdivided land plots of 100 m² each, registered under the names of Maujud, Surya, and Bari, and executed by a single seller named H. Lili in Teras Village, Carenang Sub-District, Serang Regency, Banten Province. However, verification at the Land Office revealed that the master land certificate covering an area of 600 m² remains registered under Arwi as the original owner and has never been legally transferred to the seller. Furthermore, the original certificate is held by a moneylender as collateral for the seller’s personal debt. This situation raises significant legal issues concerning the validity of the deeds, the authority of the Land Deed Official (PPAT), and legal protection for good-faith buyers. This research employs a juridical-empirical method with a normative approach, supported by direct interviews with the affected buyers. The findings indicate that the issued deeds contain both formal and substantive legal defects due to the failure to fulfill the legal requirements for the transfer of land rights as stipulated in Government Regulation No. 24 of 1997, Government Regulation No. 37 of 1998 in conjunction with Government Regulation No. 24 of 2016, and the Indonesian Civil Code. Moreover, the PPAT is considered negligent in verifying the juridical and physical data of the land, thereby potentially subject to administrative, civil, and criminal liability.